Clonal selection drives genetic divergence of metastatic medulloblastoma - Wu, Xiaochong; Witt, Hendrik; Pfister, Stefan; Korshunov, Andrey (Nature, 2012)
Medulloblastoma, the most common malignant paediatric brain tumour, arises in the cerebellum and disseminates through the cerebrospinal fluid in the leptomeningeal space to coat the brain and spinal cord1. Dissemination, a marker of poor prognosis, is found in up to 40% of children at diagnosis and in most children at the time of recurrence. Affected children therefore are treated with radiation to the entire developing brain and spinal cord, followed by high-dose chemotherapy, with the ensuing deleterious effects on the developing nervous system2. The mechanisms of dissemination through the cerebrospinal fluid are poorly studied, and medulloblastoma metastases have been assumed to be biologically similar to the primary tumour3,4. Here we show that in both mouse and human medulloblastoma, the metastases from an individual are extremely similar to each other but are divergent from the matched primary tumour. Clonal genetic events in the metastases can be demonstrated in a restricted subclone of the primary tumour, suggesting that only rare cells within the primary tumour have the ability to metastasize. Failure to account for the bicompartmental nature of metastatic medulloblastoma could be a major barrier to the development of effective targeted therapies.